Novel Psychoactive Substances : Policy, Economics and Drug Regulation - Corazza, Ornella; Roman-Urrestarazu, Andres (Springer International Publishing : Imprint: Springer, 2017)
In light of the recent emergence of New Psychoactive Substances (NPS) on a global scale, this book provides a timely analysis of the social and economic impact of the NPS phenomenon, and of the global policy and regulatory responses to it. It presents the first comprehensive overview of the international regulation, policy and market structure of the NPS phenomenon, offering a guide to inform legislative discussions and demonstrating from a comparative perspective the different approaches used to address the rise of NPS to date. It covers topics such as organized crime, drug markets, clinical evidence on NPS, and different regulatory measures. Overall, this highly informative and well-structured repository of different experiences with NPS policy, law and regulation offers an essential primary source of evidence for anyone interested in the area of drug and NPS policy, health economics and public health.